Pencegahan Tindak Pidana Narkotika Desa Sindangsari, Kuningan, Jawa Barat - Muhamad Rizal; Pani Maulana; Rhejan Gema Mahardika Bilhaq; Vinda Agustina; Virgin Elvany; Suwari Akhmaddhian; Sarip Hidayat; Haris Budiman (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
Misuse of Narcotics and illegal drugs (narkoba) is a phenomenon that has long been experienced by the countries all over the world, including Indonesia. This is basically a transnational crime, considering the chain link of the drug misuse includes production and trade activities to the countryside. Considering that this crime is an expanding chain, it is necessary to have legal counseling about the dangers and prevention of narcotics and legal aid for all regions in Indonesia, including the Kuningan Regency. Provision of legal aid is one way to realize access to law and justice for the poor which is provided by the state on the mandate of the constitution. Several regulations regarding legal aid have been issued by the state through laws and implementing regulations as well as from the Supreme Court or the Constitutional Court through Supreme Court Regulations and Constitutional Court decisions. This article will describe systematically and scientifically which takes place in Kuningan Regency, Sindangsari Village of Sindangagung District. Based on the results of counseling there are some problems in preventing narcotics crime and implementing the provision of legal aid in the community which make the provision of legal aid to rural communities less effective, therefore, it is necessary to optimize the provision of legal aid to rural communities which is an idea to response this problem to realize the access to law and justice for rural communities, especially the poor.